2016
DOI: 10.1016/j.yrtph.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The Tibetan medicine Zuotai differs from HgCl2 and MeHg in producing liver injury in mice

Abstract: quinone oxidoreductase 1 (Nqo1) and Glutamate-cysteine ligase, catalytic subunit (Gclc). In conclusion, the Tibetan medicine Zuotai and HgS are less hepatotoxic than HgCl2 and MeHg, and differ from HgCl2 and MeHg in hepatic Hg accumulation and toxicological responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 17 publications
7
47
0
1
Order By: Relevance
“…Their expression has been shown to increase in a concentration-dependent manner in the presence of heavy metal contaminants; as such, they are considered to be a good biomarker for metal exposure in aquatic invertebrates (Amiard et al, 2006), laboratory model fish (Woo et al, 2006), and free-ranging populations of fish (Chan, 1995). These results follow closely with findings by Wu et al (2016) in male Kunming mice exposed to organic-, inorganic mercury, and traditional medicines. The expression of these genes provides a way for us to evaluate mercury toxicity in medaka with the possibility of identifying mechanisms and commonalities with higher animal models.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…Their expression has been shown to increase in a concentration-dependent manner in the presence of heavy metal contaminants; as such, they are considered to be a good biomarker for metal exposure in aquatic invertebrates (Amiard et al, 2006), laboratory model fish (Woo et al, 2006), and free-ranging populations of fish (Chan, 1995). These results follow closely with findings by Wu et al (2016) in male Kunming mice exposed to organic-, inorganic mercury, and traditional medicines. The expression of these genes provides a way for us to evaluate mercury toxicity in medaka with the possibility of identifying mechanisms and commonalities with higher animal models.…”
Section: Introductionsupporting
confidence: 90%
“…Compared to MeHg, HgCl 2 primarily induces kidney and liver injury in rodents and fish (Klaassen, 2001; Lu et al, 2011a; Wu et al, 2016). However, exposure of mouse- (Van Maele-Fabry, Gofflot & Picard, 1996), sea urchin- (Marc et al, 2002), and medaka embryos (Ismail & Yusof, 2011) to HgCl 2 produced developmental toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that about 96% of IHg are in the form of cinnabar (α–HgS), and the assimilation efficiency of Hg from cinnabar was lower than 0.2%. 18, 20, 48 The bioavailability of Hg 2+ to human body from different species (excluding HgS) that are present in TTM is still under question, while the bioavailability of Hg 2+ from various food sources to human body is known to range from 0.2% to 94%. 49 Based on these values, we set the fraction of IHg assumed to be absorbed by human body in a range of 0 - 4%, and generated by the Monte Carlo simulation in the PBPK model.…”
Section: Methodsmentioning
confidence: 99%